2013
DOI: 10.1159/000351297
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the WINROP Screening Algorithm for the Prediction of Retinopathy of Prematurity in a Chinese Population

Abstract: Background: Retinopathy of prematurity (ROP) is a gestational age (GA)-related illness that can lead to blindness in premature infants. Timely screening of premature infants could improve visual prognosis. Objective: To evaluate the WINROP algorithm as a method of predicting severe ROP in a Chinese population. Methods: 590 infants with a GA <32 weeks wereentered into an online surveillance system (www.winrop.com) that included ROP evaluations and weekly weight measurements from birth to a corrected GA of 40 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
2
32
1
2
Order By: Relevance
“…The other factor contributing to the different WinROP outcomes may lie in differences in the quality of care for prematurely born neonates in Europe and the USA compared to countries where such care may not be so readily available. The importance of this factor is supported by the fact that in our study (as well as in the studies from Sweden or USA), practically no neonates born after GW 29 developed serious ROP that would require treatment 26,32,33,[38][39] while multiple cases requiring treatment were reported in the studies from Brazil, Mexico or China [35][36][37] . In attempts to use the WinROP system for predicting development of ROP (type 1 -3), all test characteristics decreased significantly.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The other factor contributing to the different WinROP outcomes may lie in differences in the quality of care for prematurely born neonates in Europe and the USA compared to countries where such care may not be so readily available. The importance of this factor is supported by the fact that in our study (as well as in the studies from Sweden or USA), practically no neonates born after GW 29 developed serious ROP that would require treatment 26,32,33,[38][39] while multiple cases requiring treatment were reported in the studies from Brazil, Mexico or China [35][36][37] . In attempts to use the WinROP system for predicting development of ROP (type 1 -3), all test characteristics decreased significantly.…”
Section: Discussionsupporting
confidence: 76%
“…So far, our results are in accordance with the results from Sweden and USA reporting 100% sensitivity (and therefore, by induction, 100% negative predictive values) (ref. 26,32,33,[38][39] ) while studies from China, Mexico, Brazil or Korea [34][35][36][37] reported sensitivity values ranging from 85% to 95%. The WinROP system correctly identified all 24 infants requiring or potentially requiring treatment (Type 1 or Type 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 and with studies of postnatal weight gain as a predictor of the development of severe ROP. [18][19][20][21][22][23][24][25][26][27][28][29] The generalizability to a diverse U.S. cohort lends support to clinical applications, including exogenous postnatal IGF-1 supplementation, which may prevent or reduce the severity of ROP, and risk prediction, particularly through the use of a more easily obtained surrogate measure such as postnatal weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…16 Slow postnatal weight gain, an assumed surrogate measure for serum IGF-1, has also been found to be predictive of severe ROP in European, North American, South American, and Asian cohorts. [18][19][20][21][22][23][24][25][26][27][28][29] Interestingly, there is increasing evidence that ethnicity may be an independent risk factor for the development of severe ROP. [30][31][32][33] However, no North American studies on IGF-1 and ROP have been reported to our knowledge.…”
mentioning
confidence: 99%